Functional MRI of inhibitory processing in abstinent adolescent marijuana users - Tapert, Susan F. (2007)
BACKGROUND: Marijuana intoxication appears to impair response inhibition, but it is unclear if impaired inhibition and associated brain abnormalities persist after prolonged abstinence among adolescent users. We hypothesized that brain activation during a go/no-go task would show persistent abnormalities in adolescent marijuana users after 28 days of abstinence. METHODS: Adolescents with (n=16) and without (n=17) histories of marijuana use were compared on blood oxygen level dependent (BOLD) response to a go/no-go task during functional magnetic resonance imaging (fMRI) after 28 days of monitored abstinence. Participants had no neurological problems or Axis I diagnoses other than cannabis abuse/dependence. RESULTS: Marijuana users did not differ from non-users on task performance but showed more BOLD response than non-users during inhibition trials in right dorsolateral prefrontal, bilateral medial frontal, bilateral inferior and superior parietal lobules, and right occipital gyri, as well as during “go” trials in right prefrontal, insular, and parietal cortices (p<0.05, clusters>943 μl). Differences remained significant even after controlling for lifetime and recent alcohol use. CONCLUSIONS: Adolescent marijuana users relative to non-users showed increased brain processing effort during an inhibition task in the presence of similar task performance, even after 28 days of abstinence. Thus, increased brain processing effort to achieve inhibition may predate the onset of regular use or result from it. Future investigations will need to determine whether increased brain processing effort is associated with risk to use.